OUTBREAK OF EXTENSIVELY DRUG RESISTANT STENOTROPHOMONAS MALTOPHILIA IN BURN UNIT - Ali, Usman; Abbasi, Shahid Ahmad; Kaleem, Fatima; Aftab, Irum; Butt, Tariq (Journal of Ayub Medical College Abbottabad, 2017)
Stenotrophomonas maltophiliais an emerging cause of nosocomial infections. We report an outbreak of XDR-Stenotrophomonas maltophilia infection from burn unit of a tertiary care hospital in July 2016. The strain isolated was resistant to all antimicrobials tested but colistin. Outbreak investigation was carried out which subsided after timely intervention. Patients were treated adequately by Colistin. Keywords: Burn unit, Outbreak; Stenotrophomonas maltophilia